The Role And Notary Responsibilities Of Establishment Of A Commanditary Fellow - Nailatul Muna; Cahaya Mutiara Mardiana Putri; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to: 1) Analyze know their roles and responsibilities in the establishment of the Guild Commanditaire Notary. 2) Obstacles encountered in implementing the Notary's role and responsibility in the establishment of the Guild Commanditaire. 3) The solution or an attempt to overcome the obstacles encountered in implementing the notary's role and responsibility in the establishment of the Guild Commanditaire.This study using sociological juridical approach or empirical legal research involves studying law from an external perspective to the object of the study of social attitudes and behavior against the law. Sources of primary data from interviews, while secondary data from literature. The study was analyzed by using a descriptive analysis.The research results are: 1). Roles and responsibilities in the establishment of the Guild Commanditaire Notary is to create legal certainty for the deed he made are authentic and can be used as a means of proving strong and when there are problems associated with the establishment of a limited partnership. Notary also instrumental in the establishment registration Kommanditgesellschaft the Ministry of Law and Human Rights through an online system that is SABU. Notary responsible for storing all documents in the manufacture of the deed of establishment. 2). The obstacles faced by the Notary is the rule about registering through SABU is still relatively new so in the field occurred constraints for example, many notaries are not yet aware of any changes to the rules and the registration mechanism.Keywords: Guild Commanditaire; Deed; SABU.